2019
DOI: 10.5897/ajar2019.14332
|View full text |Cite
|
Sign up to set email alerts
|

The role of soil nutrient ratios in coffee quality: Their influence on bean size and cup quality in the natural coffee forest ecosystems of Ethiopia

Abstract: Nutrients are essential for plant growth and development, and soil nutrient ratios play key roles in coffee quality. The objective of this study was to investigate the influence of soil nutrient ratios on the quality of wild Arabica coffee in Ethiopia. Results revealed that the balance between the soil nutrients was well correlated with coffee quality attributes. The balance between magnesium and calcium (Mg:Ca) and the balance between nitrogen and phosphorus (N:P) were found to be very important factors for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Soil nutrient content had a significant impact on the formation of cocoa bean flavor. In addition to affecting plant growth and development, specific nutrients impact metabolic functions [23]. Soil composition is also known to affect the formation of plant yields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil nutrient content had a significant impact on the formation of cocoa bean flavor. In addition to affecting plant growth and development, specific nutrients impact metabolic functions [23]. Soil composition is also known to affect the formation of plant yields.…”
Section: Discussionmentioning
confidence: 99%
“…These nutrients serve a variety of functions in plants, particularly in tissues, acting as catalysts in various reactions and osmotic regulators [25]. According to Yadessa et al [23], each nutrient affects plant growth, development, and yield quality by becoming integrated into organic compounds such as fatty, nucleic, and amino acids. These compounds, in turn, alter the chemical composition and sensory quality of the plant product.…”
Section: Discussionmentioning
confidence: 99%
“…Abebe et al [124] found relationships between cupping quality of Ethiopian coffee and several soil nutrient ratios; for example, Mg:K, P:N, and P:C ratios were all positively associated with cupping quality. However, the notion that specific cation ratios are required for optimal plant growth has been largely discredited [125], and in the absence of any other studies linking soil nutrient ratios to coffee cupping quality, it is difficult to extrapolate the results of Abebe et al (2019) [124] to draw broader conclusions.…”
Section: Soil and Fertility Managementmentioning
confidence: 99%
“…e preharvest stage facet consists of nine categories that encompass the processes that are prior to the harvest (see Figure 9). e first category, with 3.3%, is soil conditions and consists of articles that study the soil properties [56], physicochemical attributes [57], nutrition [58], fertility [59], microbiological conditions [60], and even soil color [61]and how it affects coffee quality. e category origin (8.9%) includes publications that compare the origin of coffee with the respective quality [62].…”
Section: Rq7: What Stages Of the Coffee Chain Production Arementioning
confidence: 99%